Systematic review: the use of thiopurines or anti‐TNF in post‐operative Crohn's disease maintenance – progress and prospects. Issue 11 (16th April 2014) - Jones, G. R.; Kennedy, N. A.; Lees, C. W.; Arnott, I. D.; Satsangi, J.
Summary Background Post‐operative recurrence of Crohn's disease is an important management challenge, with 2‐year recurrence rates defined by clinical, endoscopic and radiological parameters of up to 77%, 64% and 49%. Clinical and severe endoscopic recurrence vary widely in controlled trials from 13% to 36% and 22% to 56% with thiopurine treatment or 0% and 9% with infliximab treatment respectively at 1 year. Aims To provide a review of the evidence for thiopurine or anti‐TNF use in post‐operative Crohn's disease, and to assess the ability to identify those patients at highest risk of recurrent disease. Methods A literature search was undertaken using Medline, Embase and Cochrane databases to identify studies using search terms 'thiopurine', 'azathioprine', 'mercaptopurine', 'Infliximab', 'adalimumab', 'Anti‐TNF', 'Crohn's disease', 'post‐operative' and 'recurrence'. Results Trials to examine this important area have proved difficult to execute, with recruitment and retention of patients posing major challenges to randomised clinical trials. There have been four RCTs of 433 patients of thiopurine therapy (with three meta‐analyses of these data), and one of anti‐TNF therapy involving 24 patients. Overall the efficacy data for thiopurine use in this setting are inconclusive, and other than smoking, there are no consistent predictors of post‐operative relapse. Conclusions At present, evidence for routine use of thiopurine treatment in post‐operative Crohn's disease is heterogeneous and unconvincing. Stratification by risk of relapse emerges as a key challenge in post‐operative management that needs to be addressed, using clinical parameters and emerging biomarkers. The evidence for prophylactic anti‐TNF use is limited though promising, with its routine use guided by early assessment of relapse.